Ultrafast extreme thermal–electrical fabrication of volcano-shape-like core-shell Ag-MnxOy branches anchored on carbon as high-performance electrochemical electrodes. (January 2022) - Yeo, Taehan; Seo, Byungseok; Lee, Jaeho; Park, Seounghyun; Kim, Kyungmin; Choi, Wonjoon
Abstract: Rationally designed hybrids of metal/metal oxides/carbon-based materials can overcome the fundamental limits of single-material electrodes. However, their conventional synthesis causes phase/interface segregation/unintended diffusive characteristics of building blocks. Herein, we report an ultrafast extreme thermal-electrical wave (UTEW) which is a Joule heating-driven, tunable and scalable synthesis technique for unusually arranged and morphologically trapped Ag-Mnx Oy -carbon fiber (CF) electrochemical electrodes. UTEW induces thermochemical reactions passing through entire precursor mixtures of silver-manganese nitrates and CF within a few seconds. The programmable temperature ranges and heating–cooling rates/duration enable morphological traps capturing metastable phases and wetted interfaces of the constituents, thereby fabricating unique volcano-shape-like core-shell Ag-Mnx Oy branches anchored on CF (VCS-Ag-Mnx Oy -CF). The comparison with other electrodes (Ag-CF and Mnx Oy -CF) elucidate the formation mechanism of VCS-Ag-Mnx Oy -CF and the synergistic effects of rationally combined Ag-Mnx Oy -CF in electrochemical performances. The UTEW fabrication strategy will inspire fascinating hybrid electrodes and catalysts which cannot be achieved through conventional fabrication methods. Graphical Abstract: Ultrafast extreme thermal–electrical wave enables one-step fabrication of volcano-shape-like core-shell Ag-Mnx Oy branches anchored on carbon fibers for high-performance electrochemical electrodes. ga1 Highlights: Ultrafast extreme thermal-electrical waves (UTEW) enable tunable temperature/heating–cooling for hybrid material synthesis. It facilitates morphological traps capturing metastable phases and wetted interfaces of the constituents. Volcano-shape-like core-shell Ag-Mnx Oy branches anchored on carbon is fabricated through the UTEW. Unusually arranged and strongly combined active materials on carbon backbones highly enhance electrochemical reactions. They exhibit an outstanding areal capacitance (345 mF/cm 2 ) and retention (100% after 10, 000 cycles).